Role of cartilage graft in type 1 tympanoplasty: audiological and otologic outcomes - Kaur, Jasmeet; Bhagat, Sanjeev; Sahni, Dimple; Sharma, Dinesh K.; Yadav, Vishav (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Temporalis fascia is the most commonly used graft material for the tympanic membrane perforations. Due to high failure rate of temporalis fascia in adhesive otitis media, large perforations and advanced middle ear pathology alternate graft materials which are more rigid and resistant to infection are being used. Cartilage graft has shown to be a promising graft material in such cases. The purpose of this study was to evaluate the functional and anatomic results with cartilage graft in type 1 tympanoplasty. Methods: The present prospective study was conducted among 40 patients of chronic otitis media between 11-60 years of age requiring tympanoplasty in department of ear, nose and throat (ENT) in Government Medical College and Rajindra Hospital, Patiala. Results: The overall success rate of type 1 cartilage tympanoplasty was 85% in terms of perforation closure and post operative pure tone audiometry (PTA) at 6 weeks was 37.24 and at 12 weeks PTA was 34.27 The p value was <0.001 which was found to be significant. The AB gap closure at 6 weeks post op was 6.79 and at 12 weeks 9.76±2.12 dB. Conclusions: Based on the results of this study, it can be concluded that cartilage is more effective graft material in high-risk perforations, chronic ET dysfunction than fascia and audiological improvement with cartilage is found to be comparable with temporalis fascia.